State-‐owned Enterprises in China : An Analysis of Profitability, Science and Technology Development and Business Groups - Antberg, Linn Victoria (2015)
After the end of the communist era in China in the late 1970’s, a key task for the government was to restructure the state-owned enterprises into separate autonomous units and make the transition towards a more market-‐based economy. This report aims at developing an increased understanding of the SOE reorganization in China and policies related to these reforms. By extensive literature review and analysis of the most recent data, key elements of the reforms are identified and the implication and success of those are discussed. More specifically, the impact of SOE reforms on the profitability of SOEs, the development of internationally competitive domestic firms and the acquisition and development of technology and innovative capacity are evaluated. The evidence presented in this report show that the SOE reforms have been successful in increasing the profitability of SOEs, but SOEs are still lagging behind private firms in terms of profitability and efficiency and also use their R&D resources less efficiently.